Strategy used by small-scale food entrepreneurs against the impact of the covid-19 pandemic - Harifah Mohd Noor; Ubong Imang; Jurry Foo; Tatas Hardo Brotosudarmo (Universiti Teknologi MARA, 2022)
The presence of small-scale food enterprises contributes significantly to the country's income while also providing numerous job opportunities in the community. The purpose of this study was to look at how small-scale food entrepreneurs try to stay in business while dealing with the effects of COVID-19. The strategies factor was developed using factor analysis, and descriptive analysis was used to examine demography, strategy practices, and the assistance in enhancing entrepreneurial strategy. This research has identified three strategies factors: add skills, service and supply, and reduce expenses. However, entrepreneurs must enhance their strategy by utilizing government assistance. As a result, the government must be vigilant in providing entrepreneurs with the assistance they require to rehabilitate businesses affected by the COVID-19 pandemic.